Pengembangan Sistem Informasi Manajemen Magang Berbasis Web di Dinas Komunikasi, Informatika, Statistik dan Persandian Kabupaten Tuban - Adwitiya Dwi Listanto, Evan; Budi Nugroho (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Diskominfo SP Tuban requires an effective digital system to manage internship administration, participant monitoring, and digital learning processes. The previous web-based internship management system, developed using the Laravel framework with Role-Based Access Control (RBAC) and Hybrid Authentication, had several limitations: a uniform dashboard for all user roles, poor mobile responsiveness, a virtual user mechanism that prevented permanent account records, redundant database structures, the absence of an integrated e-learning feature, and profile photo synchronization issues. This study aims to develop and improve the system by: (1) redesigning the authentication flow from virtual users to permanent accounts, (2) developing role-specific dashboards for eight user types, (3) restructuring the database with seven new tables, (4) building an e-learning module supporting text, file, and YouTube video materials with a prerequisite mechanism, (5) improving responsive design for mobile devices, (6) resolving profile photo issues with gallery/camera/Google source options, and (7) adding an internship application module with supervisor search feature. Black-box testing on 15 test scenarios confirmed that all main system functions operate correctly without functional errors.